Quality Control for the Illumina HumanExome BeadChip - Igo, Robert P. (Curr Protoc Hum Genet, 2016)
The Illumina HumanExome BeadChip and other exome-based genotyping arrays offer inexpensive genotyping of some 240,000 mostly nonsynonymous coding variants across the human genome. The HumanExome chip, with its highly non-uniform distribution of markers and emphasis on rare coding variants, presents some unique challenges for quality control (QC) and data cleaning. Here, we describe QC procedures for HumanExome data, with examples of challenges specific to exome arrays from our experience cleaning a data set of approximately 7,500 samples from the NEIGHBORHOOD Consortium. We focus on standard procedures for QC of genomewide array data, including genotype calling, sex verification, sample identity verification, relationship checking and population structure, that are complicated by the HumanExome panel's enrichment in rare, exonic variation.